Synthetic Organic Chemistry of α-Imino Ketones: A Graphical Review - Pareek, Abhishek; Yaragorla, Srinivasarao (SynOpen, 2024)
α-Imino ketones are traditionally synthesized through condensing simple and readily available α-keto aldehydes or 1,2-diketones with primary or secondary amines. They are structurally similar to many naturally occurring biological substances due to the presence of the imino group (–N=C–). Chemically, C-acylimines exhibit ambiphilic reactivity, making their synthetic chemistry particularly attractive and viable for the creation of various aza-cyclic and heterocyclic compounds, including their asymmetric counterparts. Consequently, numerous synthetic strategies have been developed starting from these building blocks. Herein, we provide a graphical review of state-of-the-art synthetic efforts over the past 20 years, focusing on the use of α-imino ketones (both cyclic and acyclic) for the synthesis of small molecules and complex systems.
Keywords: α-imino ketones; C-acylimines; ambiphilic reactivity; cycloadditions; annulations; asymmetric synthesis